ChemInform Abstract: Rapid and Efficient Synthesis of 3, 3‐Di(1H‐indol‐3‐yl)indolin‐2‐ones and 2, 2‐Di(1H‐indol‐3‐yl)‐2H‐acenaphthen‐1‐ones Catalyzed by p‐TSA. Issue 48 (2nd December 2014) - Yu, Jiangxia; Shen, Tianhua; Lin, Yan; Zhou, Yongbing; Song, Qingbao
Abstract The title compounds (III) and (V) are obtained by reaction of various isatins or acenaphthenequinone, resp., with indoles under mild reaction conditions.